2004
DOI: 10.1002/bies.20152
|View full text |Cite
|
Sign up to set email alerts
|

Hold the germ cells, I'm on duty

Abstract: Germ cell segregation and gamete production are developmental problems that all sexually reproducing species must solve in order to survive. Many people are familiar with the complex social structures of some insect species, where specialised castes of adult insects perform specific tasks, one of which is usually to guard the sexually reproductive queen. The parasitic wasp Copidosoma floridanum adds another level of complexity to the caste system: a fertilised egg produces both sterile, short-lived "soldier" l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Thereafter, embryos that inherit germ cells develop into reproductive larvae which ultimately pupate and form adult wasps, while embryos that inherit only somatic cells develop into precocious (¼soldier) larvae, which lack gonads and never develop into adult wasps (Corley et al, 2005;Gordon and Strand, 2009;Zhurov et al, 2007). So germ cell specification is achieved by maternal oosome inheritance in C. floridanum (Extavour, 2004). Our results in contrast indicate that M. cingulum larvae develop from a single secondary embryonic cell, which is released from a secondary morula after many rounds of cell division (Figs.…”
Section: Pseudogerms Never Develop Into Larvaementioning
confidence: 98%
“…Thereafter, embryos that inherit germ cells develop into reproductive larvae which ultimately pupate and form adult wasps, while embryos that inherit only somatic cells develop into precocious (¼soldier) larvae, which lack gonads and never develop into adult wasps (Corley et al, 2005;Gordon and Strand, 2009;Zhurov et al, 2007). So germ cell specification is achieved by maternal oosome inheritance in C. floridanum (Extavour, 2004). Our results in contrast indicate that M. cingulum larvae develop from a single secondary embryonic cell, which is released from a secondary morula after many rounds of cell division (Figs.…”
Section: Pseudogerms Never Develop Into Larvaementioning
confidence: 98%
“…More recent studies have shown that caste fate in C. floridanum is mediated by a developmental asymmetry that results in differential allocation of germ cells to embryos (Donnell et al, 2004;Zhurov et al, 2004). Similar to other phylogenetically advanced insects, primordial germ cells (PGCs) in C. floridanum are specified early in embryogenesis via inheritance of maternal determinants (Extavour and Akam, 2003;Extavour, 2004). Unlike other insects, however, PGCs in C. floridanum proliferate substantially during the clonal phase of development and are asymmetrically parceled to embryos.…”
Section: Introductionmentioning
confidence: 97%